Is there a right number? The fragmentation of interest representation in Portuguese police unions - Rego, Raquel (International journal of police science & management, 2024)
In many countries, the right of police to unionise has still not been achieved or has only recently taken place. After decades of pressure, Portuguese police gained the right to unionise in the 21st century. Following legislation in 2002, several national police unions appeared and, in 2019, they had reached a disproportionate total of 19 unions, while working conditions were deteriorating and a Facebook-organised protest started gaining relevance. Through interviews with every police union and the police administration, complemented by secondary data, we first demonstrate how the 2002 law was a structure of opportunity enabling the proliferation of unions driven by individual motivations. Second, we portray how fragmentation of unions contributed to deadlocked negotiations leading older unions and mass media to demand new legislation. We conclude with the relevance of organisational and institutional processes into the provision of objective, predictable and proportional criteria for union representativeness.